2021
DOI: 10.1371/journal.pone.0246693
|View full text |Cite
|
Sign up to set email alerts
|

Developmental pattern of grapevine (Vitis vinifera L.) berry cuticular wax: Differentiation between epicuticular crystals and underlying wax

Abstract: The grapevine berry surface is covered by a cuticle consisting of cutin and various lipophilic wax compounds. The latter build the main barrier for transpirational water loss and protect the fruit against environmental factors e.g. pests, mechanical impacts or radiation. The integrety of the fruit surface is one important key factor for post-harvest quality and storage of fruits. Nonetheless, the developmental pattern of cuticular wax was so far only investigated for a very limited number of fruits. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
5
14
0
Order By: Relevance
“…The raisin and table grapevines had higher fruit number compared to the wild grapevine cultivars but lower than the wine grapevine cultivars ( Figure 7 ). This is in accordance with [ 21 , 26 ] that reported that wild grapevine cultivars had lower number of fruits per plant, smaller berry size, and weak berry development patterns compared to the modern wine, table, and raisin grape cultivars. This might be due to genetic variations [ 15 ], poor canopy management, and vigorous nature of wild grapevine species [ 13 , 14 ].…”
Section: Resultssupporting
confidence: 92%
“…The raisin and table grapevines had higher fruit number compared to the wild grapevine cultivars but lower than the wine grapevine cultivars ( Figure 7 ). This is in accordance with [ 21 , 26 ] that reported that wild grapevine cultivars had lower number of fruits per plant, smaller berry size, and weak berry development patterns compared to the modern wine, table, and raisin grape cultivars. This might be due to genetic variations [ 15 ], poor canopy management, and vigorous nature of wild grapevine species [ 13 , 14 ].…”
Section: Resultssupporting
confidence: 92%
“…We assume that the removal of epicuticular waxes in "Regent", "Acolon", "Pinot Noir", and "Pinot Blanc" may have resulted in a less slippery surface and better grip for D. suzukii tarsae, whereas this does not seem to be the case in "Müller-Thurgau" (Figures 2D,I). Wax crystals of "Müller-Thurgau" are quite fine, rather filamentous and relatively flat, as also recently shown by Arand et al (2021).…”
Section: Discussionsupporting
confidence: 69%
“…Overall, more flies rested and deposited more eggs on berries, whose epicuticular wax layers were removed (dewaxed), compared to intact berries except of "Müller-Thurgau" (Figures 2D,I). When berries start to touch each other during development, their wax coat appears patchier and glossy spots become visible (Arand et al, 2021). Thus, parts of epicuticular wax crystals may also be reduced under natural conditions, causing potentially higher acceptance by this fly species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition and crystal morphologies of cuticular wax were influenced by a variety of factors including development stages, species, tissues, and environmental conditions ( 2 , 4 , 17 ). Previous studies have determined the wax composition in the berries of grape cultivars and identified several related genes, including CER and WIN1, in grape genome ( 3 , 5 , 18 ). However, our knowledge on the accumulation characteristics and molecular mechanisms of cuticular wax in grape is still fairly restricted.…”
Section: Introductionmentioning
confidence: 99%